Seismic vulnerability assessment through global-and local-scale analyses for a historic masonry building constructed in 1896. (March 2023) - Uzdil, Oguz; Cosgun, Turgay; Sayin, Baris; Akcay, Cemil
Abstract: The causes of collapse in masonry buildings are different than those of reinforced concrete and steel-framed buildings. This is due to differences in structural behavior as a result of the materials and techniques used in the construction of such buildings. The most significant contribution to this behavioral difference is made by the out-of-plane behavior of masonry buildings. Therefore, in addition to overall collapse, out-of-plane behaviors of the facade walls must also be determined in such buildings. Accordingly, not only global behavior but also local behaviors should be considered while evaluating structural performance. This paper, therefore, presents a seismic performance assessment of a masonry building by global-and local-scale analyses. The examined 3-story building was constructed in 1896 and used for different purposes. Linear, nonlinear, and kinematic limit analysis approaches were used. Shear forces on the walls and inter-story drifts obtained by the linear and nonlinear analyses were analogized with the limit values envisaged in the local building codes, thus the seismic vulnerability of the building was determined. Overturning, vertical bending and lateral bending mechanisms were obtained by local analysis